2016
DOI: 10.1007/s11434-016-1145-4
|View full text |Cite
|
Sign up to set email alerts
|

Nodeless pairing in superconducting copper-oxide monolayer films on Bi2Sr2CaCu2O8+

Abstract: The pairing mechanism of high-temperature superconductivity in cuprates remains the biggest unresolved mystery in condensed matter physics. To solve the problem, one of the most effective approaches is to investigate directly the superconducting CuO 2 layers. Here, by growing CuO 2 monolayer films on Bi 2 Sr 2 CaCu 2 O 8+δ substrates, we identify two distinct and spatially separated energy gaps centered at the Fermi energy, a smaller U-like gap and a larger V-like gap on the films, and study their interactions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 32 publications
(47 reference statements)
3
78
1
3
Order By: Relevance
“…Eventually, this could be done for charge-density and spin-density wave systems, for which no theory of the Knight shift is presently available. We note that 2H-TaS 2 has a nodal charge-density wave below 75 K, with a presumably s-wave superconducting state entering below 0.6 K [17,57], which is very similar to the complex situation in the high-temperature superconductor Bi 2 Sr 2 CaCu 2 O 8+δ , in which the nodal pseudogap (probably charge-density wave) regions and isotropic s-wave superconducting regions break up into spatial domains [58]. These results are consistent with previous c-axis twist Josephson junction experiments on that material [59].…”
Section: High-field Solution For An Anisotropic Multiband Type-ii Bcmentioning
confidence: 78%
See 1 more Smart Citation
“…Eventually, this could be done for charge-density and spin-density wave systems, for which no theory of the Knight shift is presently available. We note that 2H-TaS 2 has a nodal charge-density wave below 75 K, with a presumably s-wave superconducting state entering below 0.6 K [17,57], which is very similar to the complex situation in the high-temperature superconductor Bi 2 Sr 2 CaCu 2 O 8+δ , in which the nodal pseudogap (probably charge-density wave) regions and isotropic s-wave superconducting regions break up into spatial domains [58]. These results are consistent with previous c-axis twist Josephson junction experiments on that material [59].…”
Section: High-field Solution For An Anisotropic Multiband Type-ii Bcmentioning
confidence: 78%
“…To do this properly, one needs to apply those transformations presented in Equations (82) and (83) to the time-dependent Zeeman interaction on the conduction electrons in Equation (44) and also to the Anderson-like interaction in Equation (61) that removes a local orbital electron and places it in the superconducting state and vice versa. This will cause Equations (44), (55), (61) and (62) to be rewritten in terms of the quasiparticle operators γ j,n j ,σ (k j,|| ) and γ † j,n j ,σ (k j,|| ), and will modify Equation (58). Then, the Keldysh contour method can be used to perform a microscopic theory of K S (T) in the mixed superconducting state of an anisotropic, multiband, type-II BCS superconductor.…”
Section: High-field Solution For An Anisotropic Multiband Type-ii Bcmentioning
confidence: 99%
“…Figure 2(c) shows the electron-pair bands as a function of λ for different V 0 . We see that the electron-pair band appears for E<0 because the energy spectrum is continuous for positive energy in the crystal potential given by equation (14). It means that co-tunneling of the paired electrons is required to form the energy band.…”
Section: Metastable Electron-pair Band In 2d Square Latticesmentioning
confidence: 93%
“…Unlike the sandwiched CuO 2 layers in the bulk Bi-2212, the overall electronic spectral density on the monolayer films is characterized by a large (∼ 2 eV) Mott-Hubbard-like gap 8 . In the low-energy regime, however, two distinct and spatially separated energy gaps are observed on the films: the V-shaped gap is similar to the gap observed on the BiO layer, and the U-shaped gap is identified with the superconducting nature 8 . Such an U-shaped superconducting gap is in striking contrast with the nodal gap in the d x 2 −y 2 -wave pairing symmetry [5][6][7] .…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Zhong, et. al. reported that a monolayer CuO 2 is successfully grown on the optimal doped Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-2212) substrates via molecular beam epitaxy 8 , enabling direct probe of the CuO 2 plane by scanning tunneling microscopy. Their results are interesting and important.…”
Section: Introductionmentioning
confidence: 99%